PERSEPSI SISWA TERHADAP DISIPLIN BELAJAR PPKN SELAMA PEMBELAJARAN DARING DI SMA NEGERI 1 PANGKALAN KURAS - Sri Andriani; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the implementation of an online learning system that makes all learning activities carried out online based on the regulation of the ministry of education and culture no. 15 of 2020. These online learning activities affect all aspects of the school, especially students as subjects who participate in learning activities, namely on student behavior in the aspect of discipline, including collecting assignments that are not on time, being late in joining learning, being late for attendance and so on. The students in question are students of SMAN 1 Pangkalan Kuras. Therefore, the formulation of the problem in this study is how are students' perceptions of the discipline of learning Civics during online learning at SMA Negeri 1 Pangkalan Kuras. The purpose of this study was to find out how students perceive the discipline of learning Civics during online learning at SMA Negeri 1 Pangkalan Kuras. The research was conducted at SMAN 1 Pangkalan Kuras, Pangkalan Kuras District from June 2021 to October 2021. This research method is descriptive quantitative, data collection techniques used are questionnaires (questionnaires), interviews and documentation with a sample of 102 people. Based on the results of this study, it can be concluded that students' perceptions of the discipline of learning Civics during online learning at SMA Negeri 1 Pangkalan Kuras with a percentage of 83.57%. are in the